Corruption and Legislature Size: Evidence from Brazil - Diogo Britto; Stefano Fiorin (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
This paper studies the role of council size on government corruption in Brazil. We leverage on the discontinuous relationship between the population size of municipalities and council size dictated by the law to implement a regression discontinuity design. We document a substantial positive causal effect of the number of city councilors on the incidence of corruption detected during federal audits. Results also show that hav- ing an extra councilor does not affect the size of the public budget, but in uences its composition. It increases expenditures related to public housing and recreation, which we interpret as items related to clientelis- tic policies. Finally, we find a negative relationship between council size and its productivity: namely, the numbers of legislative bills proposed by councilor and approved are both lower in municipalities with larger councils.
Keywords: D72; D73; H72; 330; Corruption; Council Size; Regression Discontinuity